Estrategias de aprendizaje para la enseñanza en estudiantes de la Unidad Educativa Especializada “María Auxiliadora” de la ciudad de Catamayo, periodo 2024. - Alvarado Alvarado, Mayra Alejandra (2025)
In the education environment, to develop effective learning strategies is critical in order to improve the teaching – learning process. However, due to the lack of appropriate methods suitable to meet students' needs, students' academic performance is limited. This paper aims to analyse the impact of learning strategies on students' teaching process. The study was conducted during 2024 at the Unidad Educativa Especializada “María Auxiliadora” in Catamayo, Ecuador. To do this, we adopted non-experimental quantitative and descriptive methods, and designed statistical analysis to examine the relationship between the variables. Also, data collection techniques were used through teacher surveys and student academic performance analysis databases. The results showed that 83% of teachers did not use appropriate learning strategies to motivate and guide students, resulting in them not being able to successfully complete tasks. In addition, 50% of teachers do not use age-appropriate teaching resources for students, reducing the effectiveness of learning. On the other hand, 46% of student’s grades were in the low range (7.00-7.37), indicating the need to implement more effective strategies. In this regard, a project-based learning-oriented teaching guide (ABP) was designed to promote more autonomous, collaborative and meaningful learning, thereby improving student interaction with the environment and the school community. Finally, teachers are advised to implement project-based learning strategies to increase active engagement, motivate and problem-solving, and achieve more inclusive and dynamic teaching.